Penerapan Akuntansi Pajak terhadap Laporan Keuangan Pada Koperasi Unit Desa Mariayu Kelapa, Bangka Barat - Hamdi, Nuah Aulia; Valianti, Reva Maria; Hendri, Edduar (Jurnal Media Akuntansi (Mediasi), 2025)
ABSTRACT This study aims to investigate the application of tax accounting. This study's objective was to ascertain how tax accounting is applied in financial reports at KUD Mariayu Kelapa in West Bangka. In order to investigate how tax accounting affects financial statements and learn the procedures for creating tax financial reports, this study applies tax accounting to fiscal financial statements. To manage fiscal financial reports in accordance with the applicable tax accounting, KUD Mariayu Kelapa uses a tax accounting application. In this study, qualitative research methods like interviews and observation were employed. The sub-focus, which examines how tax accounting is used there, primarily focuses on the fiscal financial statements of KUD Mariayu Kelapa, West Bangka. The ability to draw conclusions was made possible by the use of documentation techniques during the data analysis. Mariayu Kelapa Village Unit Cooperative has not yet produced income tax calculations and reports in accordance with the relevant tax regulations, according to the study's findings. Keywords: Tax Accounting, Fiscal Financial Reports.   ABSTRAK Tujuan dari penelitian ini adalah untuk mengkaji penerapan akuntansi perpajakan. Penelitian ini mengkaji bagaimana akuntansi pajak mempengaruhi laporan keuangan dengan menerapkannya pada laporan keuangan fiskal dan menyelidiki tata cara pembuatan laporan keuangan pajak. Akuntansi perpajakan telah digunakan di KUD Mariayu Kelapa untuk menilai apakah pengelolaan laporan keuangan fiskal telah sesuai dengan akuntansi perpajakan yang bersangkutan. Melalui penggunaan teknik dokumentasi, hasil analisis data tersebut dapat disimpulkan. Perhitungan dan pelaporan pajak penghasilan Koperasi Unit Desa Mariayu Kelapa tidak mengikuti peraturan perpajakan yang berlaku, demikian temuan kajian tersebut. Kata kunci: Akuntansi Pajak dan Pelaporan Keuangan.